Efektivitas Sistem Informasi Pelayanan Oleh Pihak Kepolisian Berbasis Web Pada Polsek Sungai Batang - Hapsah; Ilyas; Dwi Yuli Prasetyo, (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
Polri Super App is an application developed by the police specifically designed for the public to receive superior police services more quickly and easily. This research is a qualitative research. Qualitative research allows researchers to analyze the sequence of operations, recipe formulas, the meaning of various concepts, characteristics of goods and services, images, styles, cultural practices, physical models of artifacts. The results and discussions in this study are (1) The application that is expected to be able to improve the services of the Sungai Batang Police and make it easier for the public to obtain online services has not run optimally in accordance with the objectives of the formation of the Super App Application (2) The effectiveness of the use of the Polri super app system in Sungai Batang obtained results that the application of the Design Sprint method in redesigning the UI / UX of the Polri Super App application provides a systematic, effective, and efficient approach. With five structured stages, this method helps researchers understand the specific needs of users through in-depth analysis, interviews, and observations in the initial stage. (3) the main obstacles that hinder the optimization of digital-based SKCK services at the Parepare Police. One of the most obvious obstacles is the lack of socialization regarding online registration procedures. limited access to the internet and digital devices, especially for people in remote areas or those from lower-middle economic classes